Improving Learning Outcomes Using the Problem Based Learning Model in Grade IV Elementary School Science Learning - Nur Aida Utami, Imas; Nurkholis, Nurkholis; Rinto, Rinto (Annpublisher, 2023)
This study aims to improve the learning outcomes of science learning students by applying the Problem Based Learning (PBL) learning model for class IV SD. The research method used was Collaborative Classroom Action Research (PTKK) which was carried out in 2 cycles, in cycle 1 the lowest score was 60 and the highest score was 85. Then in cycle 2 the lowest score was 70 and the highest score was 95. The percentage of complete learning outcomes in cycle 1 was 63% and in cycle 2 there was an increase of 88%. As for the results of the research conducted, it can be concluded that learning with the Problem Based Learning model in learning is able to improve student learning outcomes with the assistance of audio-visual learning media, because with the model and media assistance students become more interested in participating in learning, the Problem based learning model also makes students able to think critically in class IV SDN 1 Cigadung.